Associations Between Wearing Masks and Respiratory Viral Infections: A Meta-Analysis and Systematic Review - Chen, Yiming; Wang, Yuelin; Quan, Ningbin; Yang, Jun; Wu, Yinyin (Frontiers in Public Health, 2022)
Background: Respiratory viral infections (RVIs) are a major health concern, and some previous studies have shown that wearing masks was effective in preventing RVIs, while others failed to show such effect. Therefore, a systematic review and meta-analysis was conducted to investigate the effectiveness of wearing masks. Methods: PubMed, ScienceDirect, Web of Science, the Cochrane Library, EMBASE, MEDLINE, China National Knowledge Infrastructure (CNKI), and Chinese Scientific Journal Database (VIP database) were searched for studies evaluating the effectiveness of wearing masks. An odds ratio (OR) was used for measuring the efficacy of wearing masks in preventing RVIs. Forest plots were used to visually assess pooled estimates and corresponding 95% CIs. The I2 test was used to examine the heterogeneity, and subgroup analysis was used to explore the possible explanations for heterogeneity. Sensitivity analysis was conducted to assess robustness of the synthesized results. Begg’s test and Egger’s test were used to assess the potency of publications. Results: Thirty-five studies (24,296 participants) were eligible for meta-analyses. Overall, the result showed that wearing masks was effective in preventing RVIs (OR=0.44, 95%CI: 0.33~0.59, P＜0.01); the types of RVIs might be a source of heterogeneity in the meta-analysis. The sensitivity analysis showed that the result of this meta-analysis was robust and reliable. Begg’s test showed that there was no significant publication bias, while Egger's test showed a significant publication bias. Conclusions: Wearing masks might be effective in preventing RVIs. To reduce their RVI risk, people should wear masks when they go out in public.